Pork safety across Vietnam's traditional markets: microbial contamination and vendor knowledge, attitudes, and practices - Trang Thi Huyen Le; Hoffmann, Vivian; Ambler, Kate; Murphy, Mike; Sinh Dang-Xuan; Lindahl, Johanna F.; Rajala, E.; Lam, Steven; Boqvist, S.; Unger, Fred; Hung Nguyen-Viet (Elsevier, 2026)
Foodborne diseases are a major cause of illness in low- and middle-income countries, and most are due to fresh foods sold in traditional markets. Contamination with foodborne pathogens, especially Salmonella spp., continues to be common in these markets. To better understand why this is the case, this study assessed total bacteria count (TBC) and Salmonella in pork across Vietnamese traditional markets and evaluated vendors’ food safety knowledge, attitudes, and practices, examining their associations with contamination. Data was collected in 68 markets across five provinces, with up to 10 pork vendors per market randomly selected. Microbiological data were collected through cut pork samples and cutting boards swabs (n=396), along with structured questionnaires and observations with vendors (n=486). Cutting board swabs were analyzed for TBC only, while cut pork was tested for both TBC and Salmonella. Linear and generalized linear mixed-effects models were constructed to identify risk factors for TBC and Salmonella prevalence. The overall Salmonella prevalence in cut pork was 64.4% (255/396) and was significantly higher in southern provinces (86.8%) compared to the north (47.5%, p < 0.01). TBC was high in pork and cutting boards (6.4 log10CFU/g and 6.9 log10CFU/cm2, respectively), and only 30% of the pork samples met the Vietnamese standard for TBC in fresh meat. Selling of organs was associated with a higher TBC (coefficient = 0.13, CI: 0.01–0.26, p = 0.03) and greater Salmonella risk (OR = 2.04, p = 0.009). Temperature significantly increased both outcomes (p < 0.001), while using easy-to-clean surfaces reduced TBC levels (coefficient = -0.16, CI: -0.30 to -0.01, p = 0.03). Vendors demonstrated limited food safety knowledge and mixed attitudes. Observations revealed poor hygienic practices, such as displaying pork on cardboard or cloth or lack of washing with soap and disinfectants, which was influenced by limited access to facilities and equipment. Regional differences suggested contamination levels were influenced by both environmental and market-related factors. These findings highlight the need for holistic interventions targeting an enabling environment, appropriate equipment, and behavioral incentives.